The IDL tool suite: Specifying and analyzing inter-parameter dependencies in web APIs - Barakat, Saman; Martin-Lopez, Alberto; Müller, Carlos; Segura, Sergio; Ruiz-Cortés, Antonio (SoftwareX, 2025)
Web APIs may include inter-parameter dependencies that limit how input parameters can be combined to call services correctly. These dependencies are extremely common, appearing in 4 out of every 5 APIs. This paper presents the IDL tool suite, a set of software tools for managing inter-parameter dependencies in web APIs. The suite includes a specification language (IDL), an OpenAPI Specification extension (IDL4OAS), an analysis engine (IDLReasoner), a web API, a playground, an AI chatbot, and a website. We also highlight several contributions by different groups of authors where the IDL tool suite has proven useful in the domains of automated testing, code generation, and API gateways. To date, the IDL tool suite has contributed to the detection of more than 200 bugs in industrial APIs, including GitHub, Spotify, and YouTube, among others. Also, IDL has been used to boost automated code generation, generating up to 10 times more code than state-of-the-art generators for web APIs.